2018
DOI: 10.1590/1806-9282.64.05.420
|View full text |Cite
|
Sign up to set email alerts
|

Functionality, comorbidity, complication & surgery of hip fracture in older adults by age distribution

Abstract: SUMMARY BACKGROUND Hip fractures may be the greatest complication secondary to osteoporotic disorder. The objective of this study was to determine the influence of age distribution in the functionality, comorbidity, complications and surgical features of older adults with hip fractures. METHODS A prospective cohort study was carried out from 2013 to 2014. A sample of 557 adults over 75 years old with osteoporotic hip fractures was recruited from the Orthogeriatric Unit of the León University Hospital (Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Our findings indicate that the risk of hip fracture increases with age, a result that is consistent with those of previous studies [1,29,32] among both disabled and non-disabled people, though the gradient was steeper among non-disabled individuals. Owing to the strong association between disability rate and age, the association between age and hip fracture was attenuated among disabled people.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings indicate that the risk of hip fracture increases with age, a result that is consistent with those of previous studies [1,29,32] among both disabled and non-disabled people, though the gradient was steeper among non-disabled individuals. Owing to the strong association between disability rate and age, the association between age and hip fracture was attenuated among disabled people.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies also concluded that higher fall incidence and accident rates among individuals with disabilities resulted in elevated incidence of hip fracture. For example, age-related differences in experience of hip fractures induced from the functionality, comorbidities, surgical features, baseline differences by pharmacologic treatments, complications and features at hospital discharge [1]. In addition, the conclusion of previous literature that the cognitive impairment levels were associated with the characteristics, comorbidities, pharmacology, and complications of older adults with hip fracture [2] also supports the importance of the prevention of secondary condition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The fact that the sample in our study had a higher ratio of women to men is not a characteristic of just our study; in general, this proportion is common in both clinical and social research. One possible explanation is that for cultural reasons, women are usually more open to participating in research studies than men and in clinical contexts, it can be explained by the fact that women have a higher life expectancy than men [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the average age individuals who suffer from hip fractures (HF) is 81.4 ± 8.1 years, and they are more frequent in women than in men 1,2 . At the same time, it is evident that this type of fracture causes a high comorbidity rate, with an average of 3.7 comorbidities per patient, with a high incidence of signs of cognitive deterioration and a state of acute confusion 3,4 .…”
Section: Introductionmentioning
confidence: 99%